Regulation of (Pro)Renin Receptor in Renin-Positive Smooth Muscle Cells of Kidney Arterioles in Rats with STZ-Induced Diabetes - Zsolt Razga; Gabor Kovacs; Nikolett Bódi; Petra Talapka; Mária Bagyánszki (International Journal of Nephrology)
Objective. The nephron (pro)renin receptor may play a pathophysiological role in renal disorders in hypertension or diabetes. The aim of this study was to determine the relationship of (pro)renin receptors and transdifferentiation between the renin-negative and renin-positive SMCs in the afferent arteriole by estimating the distribution of (pro)renin receptors in renin-positive and renin-negative SMCs of the afferent arteriole of kidneys in normal and streptozotocin- (STZ-) induced diabetic rats. Therefore in diabetes the renin granulation of afferent arterioles is different as in normal, the diabetes model for finding the differences to normal in distribution of (pro)renin receptors of afferent arterioles was used. Method. To estimate the number of (pro)renin receptors in arteriolar SMCs a special protocol of immunohistochemistry to stereology was followed. Results. Our results showed that on the surface of renin-positive SMCs the number of (pro)renin receptors was upregulated, while in the cytoplasm of SMCs there was downregulation in comparison to renin-negative SMCs. There is a significant difference between the number of (pro)renin receptors on the surface and in the cytoplasm of renin-positive SMCs in normal rats. These differences in the number of (pro)renin receptors were not present in rats with STZ-induced diabetes. Any other differences in the number of (pro)renin receptors between the STZ-induced diabetic and normal rats were not detected. The tissue level of angiotensin II did not change in the kidneys of STZ-induced diabetic rats. Conclusion. The distribution of (pro)renin receptors in afferent arteriolar SMCs is related to renin granulation of SMCs, but independent of angiotensin II plasma or tissue levels in the kidney.